Therapeutic Potential of Flavonoids and Tannins in Management of Oral Infectious Diseases-A Review - Kováč, Ján; Slobodníková, Lívia; Trajčíková, Eva; Rendeková, Katarína; Mučaji, Pavel; Sychrová, Alice; Bittner Fialová, Silvia (Molecules, 2022)
Medicinal plants are rich sources of valuable molecules with various profitable biological effects, including antimicrobial activity. The advantages of herbal products are their effectiveness, relative safety based on research or extended traditional use, and accessibility without prescription. Extensive and irrational usage of antibiotics since their discovery in 1928 has led to the increasing expiration of their effectiveness due to antibacterial resistance. Now, medical research is facing a big and challenging mission to find effective and safe antimicrobial therapies to replace inactive drugs. Over the years, one of the research fields that remained the most available is the area of natural products: medicinal plants and their metabolites, which could serve as active substances to fight against microbes or be considered as models in drug design. This review presents selected flavonoids (such as apigenin, quercetin, kaempferol, kurarinone, and morin) and tannins (including oligomeric proanthocyanidins, gallotannins, ellagitannins, catechins, and epigallocatechin gallate), but also medicinal plants rich in these compounds as potential therapeutic agents in oral infectious diseases based on traditional usages such as Agrimonia eupatoria L., Hamamelis virginiana L., Matricaria chamomilla L., Vaccinium myrtillus L., Quercus robur L., Rosa gallica L., Rubus idaeus L., or Potentilla erecta (L.). Some of the presented compounds and extracts are already successfully used to maintain oral health, as the main or additive ingredient of toothpastes or mouthwashes. Others are promising for further research or future applications.
Keywords: Flavonoids; rostlinné extrakty; Plant Extracts; flavonoidy; Communicable Diseases; léčivé rostliny; hydrolyzovatelné taniny; antiinfekční látky; Plants, Medicinal; Anti-Infective Agents; taniny; Hydrolyzable Tannins; infekční nemoci; Tannins